Vocabulary building through a mobile application: an analysis of its effective and affective contributions to learners? L2 acquisition process - Lattmann, Mauricio de Bortolli (2023)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão, Programa de Pós-Graduação em Inglês: Estudos Linguísticos e Literários, Florianópolis, 2023.